Mulheres educadoras na presidência da associação feminina santista (década de 1930) - Ventura, Magda Fernandes Garcia (2016)
This present study investigates the Women¿s Association of Santos (Associação Feminina Santista, or AFS) in the 1930s, identifying the leaders responsible for the development of the education of the female element and reflecting on their actions on the inner workings of school. The main sources for this reconstruction of the historical past were found, primarily, in the well preserved archives of the now extinct AFS: minutes, reports from the Board of Directors, registry books, official letters, graduation photo albums and other iconographic material. The Documentation Center of the Baixada Santista region was consulted, as well as LIAME¿s, at Unisantos. The research also resorted to printed sources, like A Tribuna¿foremost newspaper in the city of Santos ¿where iconographic material, speeches, notices on enrollment, announcements, and other information were found, in addition to digitized newspapers available at the Hemeroteca Digital Brasileira (A Noite; Correio Paulistano; Gazeta de Notícias; O Estado de São Paulo; O Paiz; among others). The profile of the heads of the board serving in the period (1930 ¿ 1940) was identified, women of the intellectual elite: their social and political actions and educational initiatives (the various courses and aspects of school practice) of the institution.